Intercellular chaperone transmission via exosomes contributes to maintenance of protein homeostasis at the organismal level. - Takeuchi, T.; Suzuki, M.; Fujikake, N.; Popiel, H.A.; Kikuchi, H.; Futaki, S.; Wada, K.; Nagai, Y. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The heat shock response (HSR), a transcriptional response that up-regulates molecular chaperones upon heat shock, is necessary for cell survival in a stressful environment to maintain protein homeostasis (proteostasis). However, there is accumulating evidence that the HSR does not ubiquitously occur under stress conditions, but largely depends on the cell types. Despite such imbalanced HSR among different cells and tissues, molecular mechanisms by which multicellular organisms maintain their global proteostasis have remained poorly understood. Here, we report that proteostasis can be maintained by molecular chaperones not only in a cell-autonomous manner but also in a non-cell-autonomous manner. We found that elevated expression of molecular chaperones, such as Hsp40 and Hsp70, in a group of cells improves proteostasis in other groups of cells, both in cultured cells and in Drosophila expressing aggregation-prone polyglutamine proteins. We also found that Hsp40, as well as Hsp70 and Hsp90, is physiologically secreted from cells via exosomes, and that the J domain at the N terminus is responsible for its exosome-mediated secretion. Addition of Hsp40/Hsp70-containing exosomes to the culture medium of the polyglutamine-expressing cells results in efficient suppression of inclusion body formation, indicating that molecular chaperones non-cell autonomously improve the protein-folding environment via exosome-mediated transmission. Our study reveals that intercellular chaperone transmission mediated by exosomes is a novel molecular mechanism for non-cell-autonomous maintenance of organismal proteostasis that could functionally compensate for the imbalanced state of the HSR among different cells, and also provides a novel physiological role of exosomes that contributes to maintenance of organismal proteostasis.